INOVASI PEMBELAJARAN BERBASIS VIDEO STREAMING DAN JARINGAN TELEKOMUNIKASI DI PERGURUAN TINGGI - Sri Hartanto; Minda Mora Purba (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2020)
ABSTRACTIn certain study programs, especially electrical engineering, informatic engineering, information system and the like there are courses in computer program design. In this case, lecturer provides the learning how to design a computer program with a specific programming language systematically and sequentially, step by step. To increase the role of lecturer of the computer program design in a college, requires the implementation of a multimedia technology that can guarantee the systematic and sequential learning, step by step, especially when in a certain condition, the student is unable to attend the computer program design course given lecturer in the class. Although it may be found the equivalent tutorial on the internet, but the student still need the learning from lecturer. On the other hand, the lecturer of the computer program design is hard to repeat the explanation of the course given at the previous meeting to the absent student in the class, as it can spend the time already allocated for the next course explanation. In this paper provided a solution to overcome these problems by creating a streaming video provider server of computer program design courses that have been given lecturers at previous meeting in class. Access to streaming video is limited, accessible only to students who follow the course of computer program design through WLAN network on the college where the student is in college and when the end of the semester, the database server containing that streaming video is deleted by the system automatically so it can be filled with video streaming of next semester lectures, so as to save bandwidth and server memory. The explanation in this paper is limited to how to access streaming video in Wireless Local Area Network (WLAN). The methodology used is to simulate WLAN network with one computer as Learning Server and two laptops as client terminal.Â Keywords: Learning Server, Wireless LAN (WLAN), program